1989
DOI: 10.1007/bf00001399
|View full text |Cite
|
Sign up to set email alerts
|

Parental care of Tilapia mariae in the field and in aquaria

Abstract: SynopsisParental care of Tilapia mariae was observed in nature (Ethiop River, Nigeria) and in aquaria with or without intruders present. In the field, 2530% of nests are guarded by one parent, normally the female. It is assumed that most missing males have deserted. Males who participate in brood care exhibit both close brood guarding and brood defence at a lower level than females, and hence seem to invest less than females. Broods were guarded under three distinct types: (1) female at the brood, male in surr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

1990
1990
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
7
0
1
Order By: Relevance
“…Some studies, however, have reported plasticity in the reproductive behaviour of T. mariae , particularly in the manner in which parental care is exhibited (Bradford et al , 2011). Specifically, while T. mariae is primarily a monogamous species (Annett et al , 1999), there is evidence of bigamy and polygamy (Schwanck, 1989; Annett et al , 1999). In this current study, the average (both absolute and potential) fecundities of T. mariae at the two sites were not significantly different although in Nigeria, King & Etim (2004) noted considerable variation in the fecundity of T. mariae from various areas.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, however, have reported plasticity in the reproductive behaviour of T. mariae , particularly in the manner in which parental care is exhibited (Bradford et al , 2011). Specifically, while T. mariae is primarily a monogamous species (Annett et al , 1999), there is evidence of bigamy and polygamy (Schwanck, 1989; Annett et al , 1999). In this current study, the average (both absolute and potential) fecundities of T. mariae at the two sites were not significantly different although in Nigeria, King & Etim (2004) noted considerable variation in the fecundity of T. mariae from various areas.…”
Section: Discussionmentioning
confidence: 99%
“…Survival prospects for unguarded young are assumed to be very low unless they are nearing the age of independence from their parents (Keenleyside 1991). Mate desertion appears to be predominantly a male phenomenon (Kuwamura 1986, Keenleyside 1991, although three cases of apparently male-only care in the biparental species Tilapia mariae in the Ethiop River, Nigeria, were described by Schwanck (1989).…”
Section: Introductionmentioning
confidence: 97%
“…This inference could be supported by the higher investment in the nest building and rearing activities during pre-spawning and egg/wriggler phase, respectively. Moreover, the possession of a territory may have higher value for males, since they could to ensure attraction of other females and to have other spawning chances if they fail in a first attempt to reproduce (Schwanck, 1989). This is especially true to species whose males establish a territory before couple formation (Perrone, 1978;Neil, 1984).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the specialization in the execution of parental duties may be the result of differential ability to perform some particular tasks. For example, males usually are bigger than females and could be more effective in the territorial defense and, therefore, they would emphasize this activity (Barlow, 1974;Schwanck, 1989;Awata & Khoda, 2004;Itzkowitz et al, 2005).…”
Section: Discussionmentioning
confidence: 99%